Processing Coconut Pulp as Chicken Feed in Segah Hamlet, Asahduren Village, Pekutatan District, Jembrana Regency, Bali - Luh Suariani; Ni Made Yudiastari; Ni Made Ayu Suardani Singapurwa; Gek Dian Dharma Yanti; I Putu Yoga Ary Nugraha (International Journal Of Community Service, 2024)
Coconut is one of the main products produced in Segah Hamlet, Asahduren Village, Jembrana Province, Bali. The PM-UPUD program aims to strengthen the development of farmer groups and MSMEs to strengthen agriculture-based community empowerment and livestock. The operational methods include counseling, direct practice, monitoring, and evaluation. PM-UPUD's partner farmer group is the Kusuma Dewi Farmer Women's Group based in Segah Hamlet. The challenges faced by the partners include the production of traditional tandusan oil and the management of chicken feed. Through PM-UPUD activities, farmer groups have the capacity and skills to make tandusan oil and process coconut pulp into chicken feed in an integrated and comprehensive manner. Farmer groups can now produce better tandusan oil and process coconut pulp into chicken feed. PM-UPUD activities can increase income and improve the community's welfare, especially group members.